Iron-catalyzed depolymerizations of end-of-life silicones with fatty alcohols; Resource-Efficient Technologies; Vol. 1, Iss. 2 - Weidauer M. Maik; Heyder B. Benedict; Woelki D. Daniel; Tschiersch M. Moritz; Kohler-Krutzfeldt A. Angela; Enthaler S. Stephan (2015, 2015)
Title screen